1980
DOI: 10.1007/bf02587098
|View full text |Cite
|
Sign up to set email alerts
|

Localized giant pseudopolyposis of the colon in ulcerative colitis

Abstract: Recently a patient with ulcerative colitis developed abdominal pain and a left upper quadrant mass. A 67Ga-citrate scintiscan showed increased activity over the mass. A barium enema demonstrated retrograde obstruction at the splenic flexure and intraluminal multilobulated tissue masses. The total abdominal colectomy specimen showed localized giant pseudopolyposis at the splenic flexure. This condition is a rare local complication of both ulcerative and granulomatous colitis. It resembles a villous adenoma on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…PPs have been described in association with ulcerative colitis (UC) as far back as 1926, although the modern identifier terminology was not used at that time[2]. Their name originated as an effort to separate them from the true neoplastic polyps, namely adenomas[3]. …”
Section: Introductionmentioning
confidence: 99%
“…PPs have been described in association with ulcerative colitis (UC) as far back as 1926, although the modern identifier terminology was not used at that time[2]. Their name originated as an effort to separate them from the true neoplastic polyps, namely adenomas[3]. …”
Section: Introductionmentioning
confidence: 99%
“…It can also produce obstruction and intussusceptions in addition to bleeding 24,25. Ulceration of polyps and subsequent hemorrhage appears to be the result of trauma caused by fecal flow and peristalsis 1,26,27. Rare cases presenting as toxic megacolon have been reported 28…”
mentioning
confidence: 99%
“…To date, FP themselves are not considered precancerous and not an indication to operate 3,15,17,19,21,26,27. Many unnecessary colectomies have been performed for inflammatory polyps 22.…”
mentioning
confidence: 99%
“…In rare cases, the polyps are present in large numbers and of a large size, and such a condition has been referred to as giant inflammatory polyposis. [4][5][6] Kelly et al 2 reported that giant inflammatory polyposis was found in 4 (4.6%) of 86 colectomized patients with IBD. A review of 53 patients with giant inflammatory polyposis revealed that two-thirds of the patients had Crohn's disease and one-third had UC.…”
Section: Discussionmentioning
confidence: 98%